백내장 수술 전후 교정시력의 변화가 없는 환자 군에서 OQAS를 이용하여 측정한 광학적 질의 변화 - 박창원; Chang Won Park; 이용은; Yong Eun Lee; 주천기; Choun Ki Joo (Daihan angwa haghoi jabji, 2013)
목적: 백내장 수술 전후에 교정시력이 동일한 환자군에서 수술 전후의 NEI-VFQ-25의 만족도와 OQAS의 결과를 이용하여 환자의 시기능 개선상태를 객관적으로 알아보고자 한다. 대상과 방법: 2011년 12월부터 2012년 2월에 수술을 받은 백내장 환자에서 술 전과 술 후 2달째에 교정시력이 0.8에서 0.8, 1.0에서 1.0으로 변화가 없는 환자 24명(24안)을 대상으로 NEI-VFQ-25 test (National Eye Institute Visual Function Questionnaire25)를 시행 하였고, OQAS (Optical Quality Analysis System)의 Objective Scatter Index (OSI), Modulation Transfer Function (MTF Cut off), Strehl ratio, Width at 50%, 10%를 측정하여 비교하였다. 결과: 백내장 술 전과 술 후에서 NEI-VFQ-25 test는 71.54 ± 14.88 (score), 85.70 ± 6.17 (score)로 환자의 시기능에 대한 만족도가 상승하였다(p=0.002). OSI는 3.13 ± 1.66 (OSI value), 1.53 ± 0.58 (OSI value)로 감소되었으며(p=0.000), MTF cut off value는 14.51 ± 6.97에서 27.63 ± 8.98으로 개선되었다(p=0.000). Strehl ratio는 0.09 ± 0.03, 0.14 ± 0.03으로 나아졌으며(p=0.000), width at 50%는 8.44 ± 3.73, 4.52 ± 1.90으로 width at 10%는 35.30 ± 15.22, 18.04 ± 8.87으로 개선되었다(p=0.000). 결론: 백내장 수술 후 시력만으로 시기능의 개선을 알 수 없는 환자에서 NEI-VFQ-25 test는 시력의 개선을 반영하였고 OQAS는 정량화된 수치를 통해 시력의 질이 향상됨을 보여주었다. <대한안과학회지 2013;54(8):1208-1212> Purpose: To evaluate objectively the improvement level of a patient’s visual function using the NEI-VFQ-25 questionnaire pre- and post-operatively and the OQAS results from the patient group who had the same corrected visual acuity pre- and post-operatively. Methods: We examined and compared the NEI-VFQ-25 test, OSI, MTF cut-off, strehl ratio, OQAS, and width at 50% and 10% in 24 eyes of 24 patients who had cataract surgery between December 2011 and February 2012. The patients’ corrected visual acuity in both eyes had no change (0.8 and 0.8) pre-operatively and 2 months post-operatively (1.0 and 1.0). Results: The satisfaction level regarding the patients’ visual function increased. The NEI-VFQ-25 test was 71.54 ± 14.88 points pre-operatively and 85.70 ± 6.17 points post-operatively. OSI decreased to 3.13 ± 1.66 (OSI value) and 1.53 ± 0.58 (OSI value), and MTF cut off value improved from 14.51 ± 6.97 (C/deg) to 27.63 ± 8.98 (C/deg). Strehl ratio was improved to 0.09 ± 0.03 and 0.14 ± 0.03, width at 50% improved to 8.44 ± 3.73 and 4.52 ± 1.90 and width at 10% improved to 35.30 ± 15.22 and 18.04 ± 8.87 pre- and post-operatively, respectively. Conclusions: The NEI-VFQ-25 test reflected the vision improvement in patients where after cataract surgery, determination of the visual function improvement only through vision would not be possible. In addition, the OQAS showed the quality of vision improved through quantified values. J Korean Ophthalmol Soc 2013;54(8):1208-1212